Exploring reproductive associations of serum polybrominated diphenyl ether and hydroxylated brominated diphenyl ether concentrations among women undergoing in vitro fertilization. Issue 5 (19th May 2020) - Ingle, Mary E; Mínguez-Alarcón, Lidia; Carignan, Courtney C; Stapleton, Heather M; Williams, Paige L; Ford, Jennifer B; Moravek, Molly B; Hauser, Russ; Meeker, John D; ,
Abstract: STUDY QUESTION: Are serum concentrations of polybrominated diphenyl ethers (PBDEs) and hydroxylated brominated diphenyl ethers (OH-BDEs) associated with IVF endpoints? SUMMARY ANSWER: Positive associations were observed for BDE153 and several OH-BDEs with IVF endpoints. WHAT IS KNOWN ALREADY: PBDEs have been voluntarily phased out of production in the USA and EU due to their persistence and toxicity to humans and ecosystems. PBDEs have been associated with implantation failure among women undergoing IVF, yet some animal studies suggest greater toxicity from their metabolites, OH-BDEs. STUDY DESIGN, SIZE, DURATION: We evaluated a subset of 215 women (contributing 330 IVF cycles) enrolled between 2005 and 2016 in a longitudinal cohort based at Massachusetts General Hospital Fertility Center. PARTICIPANTS/MATERIALS, SETTING, METHODS: The following PBDEs were quantified: 47, 99, 100, 153 and 154 and the following OH-BDEs: 3-OH-BDE47, 5-OH-BDE47, 6-OH-BDE47 and 4-OH-BDE49. Clinical endpoints of IVF treatments were abstracted from electronic medical records. Associations of log-transformed PBDEs and OH-BDEs with IVF outcomes were assessed using multivariable generalized mixed models and cluster weighted generalized estimating equation models adjusted for lipids, age, BMI, race, year of sample collection, IVF protocol and FSH levels. Outcomes were adjusted to represent a percent change in outcome with an increase equal to the magnitude of the difference between the 75th and 25th percentiles for each specific compound (interquartile range (IQR) increase). MAIN RESULTS AND THE ROLE OF CHANCE: Detection frequencies were highest for congeners 47 and 153 (82% ≥ method detection limit (MDL)) and metabolites 3 and 5-OH-BDE47 and 4-OH-BDE49 (92% > MDL). PBDE and OH-BDE geometric mean concentrations declined by up to 80% between participants recruited in 2005 and those recruited in 2016. An IQR increase of BDE153 was associated with an increase in the probability of implantation (relative risk (RR) = 1.26, 95% CI: 1.16, 1.36), clinical pregnancy (RR = 1.32, 95% CI: 1.19, 1.46) and live birth (RR = 1.34; 95% CI: 1.15, 1.54). An IQR increase in 3 and 5-OH-BDE47 was associated with increased probabilities of implantation (RR = 1.52; 95% CI: 1.11, 2.09), clinical pregnancy (RR = 1.66; 95% CI: 1.17, 2.36), and live birth (RR = 1.61; 95% CI: 1.07, 2.40). When models were stratified by race (White (86%)/Other race (14%)), associations remained positive for White women, yet inverse associations were observed for Other race women. An IQR increase in BDE47 was associated with a 46% decreased probability of clinical pregnancy (95% CI: 0.31, 0.95) for Other race women. LIMITATIONS, REASONS FOR CAUTION: Despite the long half-lives of PBDEs and OH-BDEs, exposure misclassification is possible for women who underwent multiple treatment cycles over several months or years. It is also possible another medium, such as follicular fluid would be optimal to characterize exposure. We also tested associations for multiple congeners and metabolites with multiple outcomes. WIDER IMPLICATIONS OF THE FINDINGS: Detections of serum concentrations of PBDEs and OH-BDEs were highest in the early years of the study and suggests that the phase-out of these compounds has contributed to a decrease in exposure. The negative associations found for PBDEs and IVF outcomes among other race women suggests the potential for racial disparity. Potential racial disparities in PBDE exposure and exploration of alternative flame retardants with reproductive health outcomes should be the focus of future investigations. STUDY FUNDING/COMPETING INTEREST(S): Funding for this research was supported by the National Institutes of Environmental Health Sciences (NIEHS) [R01 ES009718, ES022955, ES000002 and 009718T32ES007069]. The authors have no conflicts of interest.